(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
Accurate and precise measurement of energy consumption for the deployment of fiber-to-the-home (FTTH) network using Gigabit passive optical network (GPON) is vital to the research community to develop models for the synthesis of energy-efficient protocols and algorithms for the access network. However, lack of power consumption measurement of optical network devices in the past has led to unrealistic and/or oversimplified model being used in simulations. Usually the access network devices are assumed always on and their consumption is both traffic and time independent. Therefore, in this paper we propose an experimentally-driven approach to i) characterize the Optical Network Unit (ONU) from the power consumption standpoint and ii) develop more accurate power consumption model for the ONU. We focus on ONU since it represents the main contributor to the energy consumption of optical access network. The real data in terms of the power consumption and traffic load have been obtained from continuous measurements performed on a GPON network testbed. The measurement is limited to a maximum 100 Mbps data rate due to a limitation in the sampling rate and precision of the measurement device. However, validation has been done with theoretical power consumption model in order to prove the feasibility of the proposed model. Our measurements show that the power consumption of the ONU exhibits a linear dependence on the traffic in which the power consumption at idle mode is 11.51 W while in low power mode the power consumption is around 7.52 W.